EMU, the changing role of public debt and the revival of sovereign credit risk perception - Kai Daniel Schmid; Michael Schmidt (University of Tübingen, Faculty of Economics and Social Sciences, 2012)
Using annual data for 21 OECD countries we provide evidence of remarkable mispricing of sovereign bonds for the so-called GIIPS countries before the start of the financial crisis. Our results also qualify the view of pronounced overpricing in the crisis. In detail, we find: (i) Since the 1980s the role of public debt for the pricing of government bonds has changed twice: First-time in the aftermath of the signing of the Maastricht treaty, and again with the wake-up call due to the onset of the financial crisis. (ii) Before the financial crisis EMU member countries had de facto been perceived as a homogenous group with regard to the role of public debt for sovereign risk pricing. (iii) With the reconsideration of country-specific fundamentals the role of public debt has not only been revived but its impact upon bond yield spreads has become comparable to the time before the Maastricht treaty.
urn:nbn:de:bsz:21-opus-65710
Keywords: E43; E44; E62; 330; EMU; GIIPS; public debt; risk perception; sovereign bond yields